Disease susceptibility and development of the cytokine repertoire in the murine Leishmania major model - Fowell, D J; Bix, M; Shinkai, K; Lacy, D; Locksley, R M (European cytokine network (Montrouge), 1998)
The murine Leishmania major model has proven fertile ground for the elucidation of CD4+ T cell effector subset differentiation in vivo. The availability of a highly susceptible inbred strain, BALB/c, that develops progressive disease due to the aberrant differentiation of Th2, as opposed to protective Th1, responses, has allowed the identification of both T cell intrinsic as well as T cell extrinsic properties that combine to mediate disease outcome. The intrinsic T cell phenotype relates to the capacity of BALB/c-derived CD4+ T cells to acquire the potential to secrete IL-4 more readily than cells from other strains of mice. The extrinsic T cell phenotype relates to the creation of a T cell repertoire capable of recognizing the immunodominant parasite antigen. Together, the two traits confer the aberrant response seen in susceptible mice challenged with L. major.